POTENSI AKSESIBILITAS FASILITAS PELAYANAN PENDIDIKAN DI DESA KABUPATEN OGAN KOMERING ULU SELATAN PROVINSI SUMATERA SELATAN - Ahmad Ramadhan; Elmafatriza Elisha E (Syiah Kuala University, 2020)
AbstractGuaranteeing education for citizens is one of the mandates in the 1945 Constitution. One of the government's efforts to carry out the mandate is through development. For this reason, the government seeks to improve education facilities and access to remote villages by prioritizing education through increasing the budget for education. This effort aims to ensure that every citizen gets a proper education, especially in rural areas. However, development in Indonesia has not been fully equitable. In 2018, basic services and infrastructure will be the lowest dimensions in the preparation of the Rural Development Index (IPD) in South Sumatra. Meanwhile South Ogan Komering Ulu regency was the district with the lowest IPD in South Sumatra, which was 53.78 below the average IPD of South Sumatra. Development disparity occurs between rural and urban areas. By increasing connectivity between regions, it is expected to increase competitiveness and reduce disparity between regions through infrastructure development. Increasing connectivity and accessibility will open isolation of an area, and increase the chances of an area getting public services.This study aims to look at accessibility between villages and their potential in accessing educational facilities. The research method in this study uses 2018 PODES data sources and connectivity data between villages. The analysis uses a social networks analysis to see the potential and accessibility of villages in educational service facilities. The results of this study are expected to be input for the local government in future development planning.